UKRAINIAN PERSONALISM THROUGH THE PRISM OF OXIDENTALISM V. JANIVA - Maslyuk, Andrii (PSYCHOLOGICAL JOURNAL, 2019)
The problem of Ukrainian personalism is reflected in the work of V. Yaniva, who represents the psychology of the Ukrainian diaspora of the 20th century. The scientist comprehensively develops the issues of psychology of personality’s oxidentalism. Based on an analysis of the European psyche, V. Yaniv identifies both positive and negative features inherent to the personality of the West. The European psyche manifests itself in a harmonious combination of emotional, volitional and cognitive spheres of personality, where the latter prevails over others. To the psyche of the West, V. Yaniv contrasts the psyche of the personality of the East, where passivity, reflection, and the advantage of emotions over reason are a priority. The scientist does not accidentally analyze the psyche of a European, but in order to clarify the role and place of the psyche of the Ukrainian personality and people, in particular, to Western or Eastern values. It has been established that the western vector of development prevails in the psyche of the Ukrainian people, while Eastern tendencies are also present. For a more visual understanding of the characteristics of the psychology of the Ukrainian people, the scientist made a comparative analysis with the Russian demos. Taking into account the anthropological study of F. Volkov, who proved that the Ukrainian and Russian peoples are different, V. Yaniv established differences on a psychological level. It was found that Ukrainians are much more dynamic than Russians; Ukrainians have a psychology of harmony and tolerance, which correlates with European values and is opposite to Russian; Ukrainians expressed individualism, independence, and the Russians collectivism, the subordination of power. V. Yaniv convincingly proves that the psyche of the Ukrainian people develops in line with Western values and is fundamentally different from the psyche of the Russian people, which is inherent in the values of the east.